2021
DOI: 10.32505/jl3t.v7i1.2803
|View full text |Cite
|
Sign up to set email alerts
|

WhatsApp and English Learning: Students’ Perceptions and Challenges in Pandemic Era

Abstract: Since the pandemic era due to Covid-19, WhatsApp has become an application that is widely used for online learning. In the new normal era, WhatsApp was still the application most widely used by lecturers and students because sending teaching materials was easy and fast. This study investigated students’ perceptions and challenges of utilizing WhatsApp in English language learning amid the pandemic era. The method used was a qualitative method. The researcher used a purposive sampling technique in selecting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
3
0
1
Order By: Relevance
“…Thus, the present study rejects the fourth null hypothesis that WhatsApp-based instruction does not have positive effect on improving the experimental group's performance in English writing composition. These findings are consistent with those reported by Ajid et al (2018); Saleh (2019); Juliana (2021) and Khan et al (2021). Furthermore, the interview findings indicated that the participants have positive perception of the WhatsApp usefulness in learning English writing composition.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, the present study rejects the fourth null hypothesis that WhatsApp-based instruction does not have positive effect on improving the experimental group's performance in English writing composition. These findings are consistent with those reported by Ajid et al (2018); Saleh (2019); Juliana (2021) and Khan et al (2021). Furthermore, the interview findings indicated that the participants have positive perception of the WhatsApp usefulness in learning English writing composition.…”
Section: Discussionsupporting
confidence: 89%
“…With rapid internet connectivity in Mauritius, learners have fast access to these learning resources which are customized by them in their attempt to find solutions to their online learning tasks. However, in many other contexts, this opportunity may not exist due to the digital divide (Nasution & Munandar, 2023;Rena, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…(Sahid, 2021). Koneksi internet, kuota internet, dan kapasitas penyimpanan di perangkat mereka masih menjadi tantangan tersendiri bagi para pelajar (Juliana, 2021). Kendala yang dialami guru selama pembelajaran daring yaitu aplikasi pembelajaran, jaringan internet dan gawai (handphone), pengelolaan pembelajaran, penilaian, dan pengawasan.…”
Section: Pendahuluanunclassified